Social Capital as a Livelihood Support for Women on the Southern Slopes of Merapi - Hastuti Hastuti; Sri Agustin Sutrisnowati (JPG (Jurnal Pendidikan Geografi), 2023)
This study reveals that the social capital that women use as a source of income is also a difficulty for them. The study was conducted based on quantitative descriptive and associations to define the pattern and distribution of phenomena, which was strengthened by reduction, classification, and interpretation of field-specific research findings. Women are dominated by the age group of less than 40 years old, with the highest level of education being SMA, and the work of farmers, while being dominated by a restricted land tenure of less than 0.1 hectares and an income of less than 2,667,000.00 rupiah. Social capital derives from social networks, primarily non-family kinships such as religion and activist links in the arts. Social capital derived from social networks is the most popular option among women in the research field. Socioeconomic network-based social capital is dominated by arisan activities. The largest social capital, based on the confidence of neighbors, results from the highest social ideals and norms of the rewang and the highest engagement in social organizing activities by the PKK. Women with social capital frequently meet food and non-food demands, such as social charges, school tuition, health, and house repairs. Women utilize social capital to sustain their social, cultural, and economic well-being. In the studied area, it can be challenging for women to fulfill their social, cultural, and economic commitments associated to community activities.